2015
DOI: 10.1177/0300060514558898
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum mean platelet volume in testicular torsion

Abstract: Objective: To compare the serum mean platelet volume (MPV) in patients with testicular torsion and healthy control subjects. Methods: This retrospective study compared clinical and demographic data from patients who underwent surgery for testicular torsion and healthy controls. Testicular torsion was diagnosed with a physical examination and Doppler ultrasonography. Age, leukocyte count, platelet count and MPV were recorded for all participants. Results: A total of 50 patients with testicular torsion and 51 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…Numerous studies have reported that haematologic parameters can be used for the differential diagnosis of TT (Bitkin et al, ; Cicek, Togan, Akbaba, Narci, & Aygun, ). But to our knowledge, only one study by Jang et al have reported the association between haematologic parameters and the testicular salvage rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that haematologic parameters can be used for the differential diagnosis of TT (Bitkin et al, ; Cicek, Togan, Akbaba, Narci, & Aygun, ). But to our knowledge, only one study by Jang et al have reported the association between haematologic parameters and the testicular salvage rate.…”
Section: Discussionmentioning
confidence: 99%
“…Whether MPV can be used to diagnose TT remains controversial. Cicek et al, () retrospectively analysed MPV in 50 children with TT and 51 normal children and found that MPV had some diagnostic value for TT. In contrast, Güneş et al, () reported that MPV did not have diagnostic ability for TT, but NLR did, by comparing 75 TT patients with 56 age‐matched healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Several studies have evaluated the diagnostic value of MPV in AA; nevertheless, some of them advocate for an increase, while some others advocate for a decrease, in MPV levels. RDW is a measure of the variability of red blood cell size and has been shown to predict various inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cicek et al studied serum mean platelet volume (Cicek, Togan, Akbaba, Narci, & Aygun, 2015), Turedi et al studied plasma SCUBE-1 levels (Turedi et al, 2015), and Yilmaz et al studied plasma d-dimer levels . Cicek et al studied serum mean platelet volume (Cicek, Togan, Akbaba, Narci, & Aygun, 2015), Turedi et al studied plasma SCUBE-1 levels (Turedi et al, 2015), and Yilmaz et al studied plasma d-dimer levels .…”
Section: Xue Et Al Investigated the Effect Of Gradual Low-flow Repermentioning
confidence: 99%
“…Several studies have been performed to identify biomarkers for testicular torsion. Cicek et al studied serum mean platelet volume (Cicek, Togan, Akbaba, Narci, & Aygun, 2015), Turedi et al studied plasma SCUBE-1 levels (Turedi et al, 2015), and Yilmaz et al studied plasma d-dimer levels . IMA is caused by reactive oxygen derivatives resulting from ischaemia-modifying albumin (Can & Yosunkaya, 2017).…”
Section: Xue Et Al Investigated the Effect Of Gradual Low-flow Repermentioning
confidence: 99%